Translate and create: the experience of transcreation in a poem by E. E. Cummings - Garcia, Pamela Angela Medina (2023)
The theory of poetic transcreation, proposed by the concrete poets Haroldo and Augusto de Campos, leaders of the Noigandres group, proposes understanding translation as a form of creation and knowledge of the poem. Aligned by the ideas of concretism in which the poem is conceived as a combination of formal graphic-phonetic and spatial elements that make an experience possible, the poets-translators understood that their work favored a metalinguistic practice that apprehends the interior of the poem and makes the translation in a search that is not limited to meaning but to sign and matter. In this sense, for those from Campos, translating is studying, but, at the same time, creating. Based on these ideas, this research aims to problematize the concept of transcreation from the translation of a famous poem by the American author Edward Estlin Cummings “a leaf falls” (1958), previously worked by Octavio Paz and Augusto de Campos. We propose that the transcreation of Cummings' piece, the comprehension and analysis exercise, allows the appearance of a poem that recovers the formal and visual intention of the sign.